Photogrammetry as a virtualization resource in the dissemination and digital preservation of tangible heritage - Leija-Román, David Alonso; Valle-Chavarría, Lorena Gertrudis; Montes-Rojas, Mª Luisa (Revista General de Información y Documentación, 2022)
This work exposes the application of a workflow model with suggested actions, so that the virtualization by photogrammetry of tangible heritage is preserved and disseminated digitally through information packages enriched with parameters of norms and good practices that complement in an accessible way the heritage documentation processes in digital format. In principle, conceptual considerations on digitization and virtualization by photogrammetry are exposed; as well as the notion of digital heritage for purposes of dissemination and long-term digital preservation of derived objects. Next, the formats and digital residuals of the photographic capture and recording process for the production of 3D objects by basic photogrammetry applied to a sculptural sample are analyzed. Lastly, technical applications are aligned and established in the residual formats of the documentary process, to evaluate and integrate information packages for long-term digital dissemination and preservation purposes.